Development Of Tasks And Rubrics To Measure Physics Practical Skills Of From Four Students Using Direct Observation And Written Test - Liew, Sang Sang (2017)
Utilising practical work in physics learning can enhance students’ understanding of abstract concepts and theories. Students need to have good mastery of practical skills so that practical work is effective in enhancing learning. In Malaysia, students’ practical skills are assessed through school based assessment and written test, which emphasize on the written work produced by students. However, there is no specific guideline to assess physics practical skills which should be assessed in the actual setting where practical work is being carried out.